Functional identification of DNA demethylase gene CaROS1 in pepper (Capsicum annuum L.) involved in salt stress - Ou, Xuelian; Hua, Qingzhu; Dong, Jichi; Guo, Kexian; Wu, Minghua; Deng, Yinjun; Wu, Zhiming (Frontiers in Plant Science, 2024)
REPRESSOR OF SILENCING 1 (ROS1) is a DNA demethylase that plays a crucial regulatory role in plants in response to various abiotic stresses. However, its role in pepper remains unclear. We selected and cloned a ROS1 gene in pepper, named CaROS1 (LOC107843637). Bioinformatic analysis showed that the CaROS1 protein contains the HhH-GPD glycosylase and the RRM_DME domains. qRT-PCR showed that CaROS1 was highly expressed in young and mature fruits of pepper and rapidly induced by salt stress. The function of CaROS1 in the salt stress response was investigated by gene silencing in pepper and overexpressing in tobacco. CaROS1-silenced pepper were more sensitive to salt stress, and their ROS levels, relative conductivity, and malondialdehyde content were significantly higher in leaves than those of the control plants. Furthermore, CaROS1overexpressing tobacco plants were more tolerant to salt stress, with a higher relative water content, total chlorophyll content, and antioxidant enzyme activity in leaves compared to those of WT plants during salt stress. These results revealed the CaROS1 has a function in salt stress response and provide a theoretical basis for salt stress tolerance molecular breeding in pepper.